The Effect of Dosage and Application Interval of Tofu Waste Liquid Organic Fertilizer on the Growth and Yield of Tomato (Lycopersicum esculentum) - Phebian Adam Pahlevy; Djarwatiningsih Djarwatiningsih; Felicitas Deru Dewanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Tofu liquid waste contains organic materials that can be utilized as liquid organic fertilizer (LOF). This study aims to determine the effect of dose and interval of LOF from tofu liquid waste on tomato plants (Lycopersicum esculentum. L). This study, conducted from April to July 2024 in Gajah Bendo Village, Pasuruan, examined the impact of tofu liquid waste-based Liquid Organic Fertilizer (LOF) on tomato plants (Lycopersicum esculentum. L). Utilizing a Completely Randomized Design (CRD) with two factors in triplicates, the researchers tested four dosage levels (0, 100, 200, and 300 ml/plant) and three application intervals (6, 10, and 14 days).  The results of the study found that the combination of LOF tofu liquid waste dosage at a dose of 300 mL/plant with an application interval of 14 days resulted in the fastest flowering age compared to other treatment combinations. However, the combination of dosage and application interval treatments did not significantly affect the parameters of plant height, number of fruits, and fruit sets. The LOF application even tended to reduce the harvest weight of tomato fruit compared to the control treatment. Future research can focus on the optimal fermentation time of liquid waste to prepare LOF and apply the LOF on tomato plants under more controlled conditions such as in a greenhouse.